Historia@60: Reflection and renewal (Historia, 2021)
EnglishHistorians have a future. We may be averse to forecasting, we become exasperated by the presentism we encounter all around us, and we are critical of narratives that portray the inevitable, forward march of history. But in our own work, we seek to innovate and to break old boundaries - be it through new interpretations, new methodologies, new forms of collaboration, and new means of disseminating our research. We are constantly engaged in renewal and reflection. Anniversaries are moments when we highlight this ongoing pursuit, and Historia's sixtieth anniversary is precisely such a moment. It is not merely a matter of looking back. It is also an opportunity to appreciate the differences and similarities between the past and the present, to take stock of the historical pursuit and to consciously delineate the direction in which we are headed. That is what Historia seeks to do. We need to consider the landscape in which we find ourselves, to understand the direction in which our discipline is headed - and moreover, to chart our path therein. This is expressed in our new cover, which is a visualisation of our endeavour to reflect and renew.   AfrikaansHistorici het 'n toekoms. Ons mag dalk 'n hekel aan voorspellings hê, die beheptheid met die hede is dikwels 'n bron van ergernis en ons staan krities teenoor narratiewe wat die onvermydelike opmars van die geskiedenis veronderstel. Tog streef ons in ons eie werk na vernuwing en die aftakeling van ou grense, hetsy deur nuwe vertolkings, metodes, vennootskappe - of geleenthede om die vrug van ons arbeid te versprei. Ons is deurlopend besig om te besin en te vernuwe. Herdenkings is oomblikke waneer ons hierdie strewe belig, en Historia se sestigste herdenking is juis só 'n oomblik. Dit gaan nie net daaroor om terug te kyk nie. Dit is ook 'n geleentheid om na te dink oor die verskille en die ooreenkomste tussen die hede en die verlede, om te besin oor die historiese strewe en om doelbewus die rigting waarin ons beweeg uit te stippel. Dit is waarna Historia streef. Ons moet die landskap waarin ons onsself bevind in oënskou neem, ons moet die rigting waarin ons vakgebied beweeg begryp en ons moet ons weg karteer. Ons nuwe voorblad is 'n uitbeelding van hierdie strewe na besinning en vernuwing.